Electronic Nose based on Poly(vinylidene fluoride)-modified Nanofibers for Discriminative Detection of Volatile Organic Compounds - Braunger, Maria Luisa [UNESP]; De Santana Gois, Bruno H. [UNESP]; Fier, Igor; De Oliveira, Vinicius J. Rodrigues [UNESP]; Da Silva Agostini, Deuber Lincon [UNESP]; Riul, Antonio; De Almeida Olivati, Clarissa [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Two e-nose setups formed by similar sensing units based on nanofibers and drop-cast films of poly(vinylidene fluoride) (PVDF) were compared. In both setups, the sensing units were formed by pristine PVDF and PVDF modified with conducting polymers. The e-noses were tested in a custom-made chamber with volatile organic compounds (VOCs) and ammonia, using dry nitrogen as a flow gas. Overall, both e-nose devices discriminate against almost all vapors, especially ammonia. The results suggest that the e-nose based on nanofibers can distinguish ethanol from isopropanol, which is not possible with the e-nose based on drop-cast films of the same materials.
Keywords: ammonia; electronic nose; electrospinning; gas sensor; PVDF; sensor array; VOC